Treatment of Heart Failure with Sodium-Glucose Cotransporter 2 Inhibitors and Other Anti-diabetic Drugs - Thomas A Zelniker; Eugene Braunwald (Cardiac Failure Review)
Patients with type 2 diabetes are at increased risk of developing heart failure, cardiovascular death and renal failure. The recent results of three large sodium-glucose cotransporter 2 inhibitor cardiovascular outcomes trials have demonstrated a reduction in heart failure hospitalisation and progressive renal failure. One trial also showed a fall in cardiovascular and total death. A broad spectrum of patients with diabetes benefit from these salutary effects in cardiac and renal function and so these trials have important implications for the management of patients with type 2 diabetes. Selected glucagon-like peptide 1 receptor agonists have also been shown to reduce adverse cardiovascular outcomes.